Research Report: The Paderborn Approach in Discourse Analysis: "The Structure of Gender Relations. Archaeology and Genealogy of the Gender Difference in the Discourse About Culture Crisis Around 1900" - Bublitz, Hannelore (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2007)
URN: urn:nbn:de:0114-fqs0702P63